2023
DOI: 10.31616/asj.2022.0053
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study with a 2-Year Follow-up of Clinical Results, Fusion Rate, and Muscle Bulk for Uniportal Full Endoscopic Posterolateral Transforaminal Lumbar Interbody Fusion

Abstract: Postoperative evaluation of the cross-sectional area of paraspinal muscle and clinical findings in patients who had interlaminar route uniportal full endoscopic posterolateral transforaminal lumbar interbody fusion (EPTLIF) after 2 years. Overview of Literature: There are limited short-term follow-up studies on efficacy, safety, and physiological changes with a 2-year follow-up. There is no study on paraspinal muscle cross-sectional area change in patients who had undergone uniportal EPTLIF. Methods: We evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Likewise, spinal surgery using an endoscope is likely to have a bigger market in the future; some spine surgeons are already performing fusion surgery using an endoscope. 22 23 24 25 26 27 28 29 30) Spinal surgeons who are not yet trained in endoscopic surgery need to prepare in advance, so they do not fall behind the trend.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, spinal surgery using an endoscope is likely to have a bigger market in the future; some spine surgeons are already performing fusion surgery using an endoscope. 22 23 24 25 26 27 28 29 30) Spinal surgeons who are not yet trained in endoscopic surgery need to prepare in advance, so they do not fall behind the trend.…”
Section: Discussionmentioning
confidence: 99%
“…The best surgical treatment option for lumbar spinal stenosis (LSS) must be decompression [1]. There have been trials, and several techniques have been developed under the name of "sufficient decompression," showing their own benefits and limitations [2][3][4]. In early 1990, subtotal laminectomy with wider decompression showed clinical success rates of 78%-88% in the early postoperative period, which decreased to approximately 70% at 1 year and approximately 50% in 5 years [5,6].…”
Section: History Of Decompression From a Technical Perspectivementioning
confidence: 99%
“…Recent developments in endoscopy-assisted spine fusion surgeries have demonstrated clinical and radiological outcomes comparable to those of conventional open surgery [ 112 115 ], emphasizing the need for specialized cage designs suitable for minimal incision techniques. Recently, Kim et al [ 116 ] demonstrated the feasibility of using a larger cage originally designed for LLIF in biportal endoscopic TLIF to achieve a favorable fusion rate ( Fig.…”
Section: Evolution Of Cage Materials In Lumbar Interbody Fusionmentioning
confidence: 99%